A novel approach for radiotherapy dose escalation in rectal cancer using online MR-guidance and rectal ultrasound gel filling – Rationale and first in human. (November 2021) - Gani, Cihan; Lo Russo, Monica; Boeke, Simon; Wegener, Daniel; Gatidis, Sergios; Butzer, Sarah; Boldt, Jessica; Mönnich, David; Thorwarth, Daniela; Nikolaou, Konstantin; Zips, Daniel; Nachbar, Marcel
Highlights: First-in-human application of a weekly online adaptive MR-guided radiotherapy boost. Rectal ultrasound gel filling facilitated excellent tumor visualization and sparing of healthy mucosa. Treatment was very well tolerated with only minimal toxicity. Abstract: Introduction: Dose escalated radiotherapy has previously been investigated as a strategy to increase complete response rates in rectal cancer. However large safety margins are required using cone-beam computed tomography guided radiotherapy leading to high doses to organs at risk or insufficient target volume coverage in order to keep dose constraints. We herein present the first clinical application of a new technique for dose escalation in rectal cancer using online magnetic resonance (MR)-guidance and rectal ultrasound gel filling. Methods: A 73-year-old patient with distal cT3a cN0 cM0 rectal cancer was referred for definitive radiochemotherapy with the goal of organ preservation after multidisciplinary discussion. A dose of 45 Gy in 25 fractions with a stereotactic integrated boost to the primary tumor of 50 Gy with concomitant 5-fluorouracil was prescribed. Furthermore, a boost to the primary tumor with 3 Gy per fraction using the adapt-to-shape workflow on a 1.5 T MR-Linac was planned once weekly. For the boost fractions 100 cc of ultrasound gel was applied rectally in order to improve tumor visibility and distancing of uninvolved rectal mucosa. In order to determine the required planning target volume margin diagnostic scans of ten rectal cancer patients conducted with rectal ultrasound gel filling were studied. Results: Based on the ten diagnostic scans an average isotropic margin of 4 mm was found to be sufficient to cover 95% of the target volume during an online adaptive workflow. Three boost fractions were applied, mean treatment duration was 22:34 min. Treatment was well tolerated by the patient with no more than PRO-CTCAE grade I° toxicity of any kind. The rectal ultrasound gel filling resulted in superior visibility of the tumor and reduced the dose to the involved mucosa especially in the high dose range compared with a boost plan calculated without any filling. A considerable tumor shrinkage was observed during treatment from 17.43 cc at baseline to 4 cc in week four. Conclusion: This novel method appears to be a simple but effective strategy for dose escalated radiotherapy in rectal cancer. Based on the encouraging observation, a prospective trial is currently under preparation.